Arthroscopically Assisted Reconstruction of Lateral Metatarsosesamoid Suspensory and Lateral Metatarsophalangeal Collateral Ligaments in the Management of Iatrogenic Hallux Varus Deformity - Charles Churk Hang Li, M.B.Ch.B., F.H.K.C.O.S., F.H.K.A.M.; Tun Hing Lui, M.B.B.S. (H.K.), F.R.C.S. (Edin.), F.H.K.A.M., F.H.K.C.O.S.; Amanda Mun Yee Slocum, M.B.B.S. (H.K.), F.R.C.S.Ed. (Orth.), F.H.K.A.M., F.H.K.C.O.S. (Arthroscopy Techniques)
The medial and lateral metatarsosesamoid suspensory ligaments together with the sesamoid apparatus are the main contributors to the rotational stability of the first metatarsophalangeal joint (MTPJ). Rotational instability of first MTPJ is a major factor in the development of hallux valgus and varus deformities. As the great toe starts to rotate, the muscle pulls across the first MTPJ, causing it to become imbalanced and lead to progressive medial or lateral deviation of the great toe. The gold standard and most reliable option for hallux varus deformity is first MTPJ fusion. However, it results in stiffness and loss of joint function and is reserved for arthritic and stiff first MTPJ. Flexible iatrogenic hallux varus is corrected by optimally anatomic ligament reconstruction. The purpose of this Technical Note is to describe the details of arthroscopically assisted reconstruction of lateral metatarsosesamoid suspensory and lateral metatarsophalangeal collateral ligaments in management of iatrogenic hallux varus deformity. We reconstruct the lateral metatarsosesamoid suspensory ligament to restore the rotational stability of the first MTPJ in hallux varus deformity. This together with reconstruction of the lateral metatarsophalangeal collateral ligament anatomically corrects both the medial deviation and rotation deformity of the great toe.